ANALISIS PENDAPATAN USAHA BUDIDAYA TAMBAK DI DESA PETIKU KECAMATAN LONGKALI KABUPATEN PASER - Yulianti; Bambang Indratno Gunawan; Elly Purnamasari (Jurnal Pembangunan Perikanan dan Agribisnis, 2023)
The purpose of this research is to find out the cost and profit and know the feasibility analysis of the business. This study used purposive sampling methods. Data analysis uses methods of production cost as well as profit analysis and business feasibility analysis. According to the results of the cost analysis incurred is Rp14.721.198,89/respondent/production, profit is Rp16.806.801,11/respondent/production, R/C value of 2,14, payback period of 4.51 times production.